Prace Paula Otleta a World Wide Web - Kotuła, Sebastian D. (Biblioteka Uniwersytecka w Poznaniu, 2013)
W projektach Paula Otleta daje się wskazać podobieństwa do systemu hipertekstowego World Wide Web. Badacze wywodzący się z różnych środowisk (m.in. medioznawczych, socjologicznych, informatycznych, bibliologiczno-informatologicznych) zwracają uwagę na podobieństwa pomiędzy projektami systemu informacyjno-wyszukiwawczego Otleta a WWW. Celem artykułu jest próba odpowiedzi na pytania, czy projekty Otleta są zbieżne pod pewnymi względami z WWW oraz czy tworząc Web, wzorowano się na pracach Otleta.

Paul Otlet’s visualizations of data integration seem to have some distinct parallels with the hypertext used in the World Wide Web. Researchers representing different disciplines (e.g., media specialists, sociologists, IT specialists and librarians) all indicate essential similarities between the attempts at the information and search system conceived by the Belgian author and visionary and that of the WWW. Accordingly, the article aims at finding an answer to the question whether Otlet’s visualizations are convergent to a certain degree with the WWW and whether the authors of the Web modeled their work on the Otlet’s achievements?
The influence of Paul Otlet upon the World Wide Web
Keywords: World Wide Web; Paul Otlet